2014
DOI: 10.1063/1.4876229
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of critical superconducting current in thin doubly-connected Sn films in an external perpendicular magnetic field

Abstract: We report the results of experimental and theoretical studies of critical current oscillations in thin doubly-connected Sn films in an external perpendicular magnetic field. The experiments were performed on samples that consisted of two wide electrodes joined together by two narrow channels. The length of the channels l satisfied the condition l ≫ ξ (ξ is the Ginzburg–Landau coherence length). At temperatures close to the critical temperature Tc, the dependence of the critical current Ic on average external m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Additionally, many computationally advanced models based on Ginzburg-Landau theory have been developed [22,24,25]. Here, we have shown that a simple model based on a linear CPR provides excellent fits to our critical current data.…”
Section: Current-phase Relationshipmentioning
confidence: 74%
See 3 more Smart Citations
“…Additionally, many computationally advanced models based on Ginzburg-Landau theory have been developed [22,24,25]. Here, we have shown that a simple model based on a linear CPR provides excellent fits to our critical current data.…”
Section: Current-phase Relationshipmentioning
confidence: 74%
“…Furthermore, we observe that the regions of stability of the vorticity, namely the Little-Parks diamonds [24,31,32], can overlap significantly, thus generating multivaluedness of the critical current and of the vorticity at a fixed magnetic field. Yet we find some magnetic field -bias current parameter regions, which we call uniquevorticity diamonds, in which only one vorticity is stable.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since ( ) varies with temperature while remains fixed, the CPR of such weak links is strongly temperature dependent. Generally, lowering the temperature transforms the CPR from sinusoidal to a sawtooth-like function, which ultimately turns into multivalued relations once ≳ 3.5 ( ), corresponding to the nucleation of phase-slip centres [33,34,35]. The multivalued CPR manifests itself as a hysteretic ( ) relation, which is a well-known characteristic of constriction junctions at ≪ [36,37].…”
Section: Discussionmentioning
confidence: 99%